2009
DOI: 10.1007/s00381-008-0780-8
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma multiforme in children: experience at Hospital Infantil de Mexico Federico Gomez

Abstract: Sixteen patients were identified. Mean age of presentation was 8.8. An increased frequency of complications was observed in younger patients and longer survival rates in patients with greater resections; main mode of presentation was directly related to intracranial hypertension; size of tumor was not related to evolution or outcome. Modern histological classifications especially designed for children are deemed necessary to accurately diagnose GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
1
12
0
2
Order By: Relevance
“…In intracranial GBM, the mean age at presentation was 8.8-13 years in the literature. 35,47 The present study showed the mean age at presentation for primary spinal GBM was 10 ± 5.1 years. For intracranial GBM, studies have shown a male predominance.…”
Section: Discussionmentioning
confidence: 48%
“…In intracranial GBM, the mean age at presentation was 8.8-13 years in the literature. 35,47 The present study showed the mean age at presentation for primary spinal GBM was 10 ± 5.1 years. For intracranial GBM, studies have shown a male predominance.…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, GBM accounts for no more than 3-15% of primary central nervous system (CNS) tumors in children (2)(3)(4)(5)(6)(7). This is despite the fact that CNS tumors are the most common solid tumors of childhood, and 40-50% of these tumors are constituted by the astrocytomas (8).…”
Section: Introductionmentioning
confidence: 81%
“…[9] However, secondary GBMs arise from other astrocytomas after years. [10] There are reports from other centers on pediatric GBM [Table 3]. We studied GBM in young age (20 years or less) during 18 years from 1990 to 2008.…”
Section: Discussionmentioning
confidence: 99%